Platelet-Rich Plasma Therapy in Premature Ovarian Insufficiency: A Case Series of IVF Outcomes - Nulianti R; Lubis S; Madjid TH; Permadi W; Adriansyah PNA; Nisa AS (International Medical Case Reports Journal)
Rina Nulianti,1 Syahnural Lubis,2 Tita Husnitawati Madjid,1 Wiryawan Permadi,1 Putri Nadhira Adinda Adriansyah,1 Aisyah Shofiatun Nisa1 1Department of Obstetric and Gynecology, Faculty of Medicine, Universitas Padjadjaran, Dr. Hasan Sadikin General Hospital, Bandung, Indonesia; 2Department of Obstetrics and Gynecology, Anugerah Bunda Khatulistiwa Hospital- Morula IVF, Pontianak, IndonesiaCorrespondence: Rina Nulianti, Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Padjadjaran, Jl. Pasteur No. 38, Bandung, West Java, 40161, Indonesia, Email rina2003@mail.unpad.ac.idIntroduction: Premature ovarian insufficiency (POI) leads to the early loss of ovarian function before age 40, resulting in infertility and hormonal imbalance. Despite the use of assisted reproductive technologies (ART), success rates remain low in this population. Platelet-rich plasma (PRP) therapy is emerging as a potential adjunct to enhance ovarian reserve.Case Illustration:Case 1: A 25-year-old nulliparous woman with a history of ectopic pregnancy and an anti-Müllerian hormone (AMH) level below 1 ng/mL received two PRP injections scheduled between days 7 to 12 of her cycle. After the first injection, her AMH level remained < 0.5 ng/mL. Following the second PRP injection, her AMH level increased to > 0.5 ng/mL. A frozen embryo transfer resulted in a successful term pregnancy and healthy newborn.Case 2: A 36-year-old nulliparous woman, married for seven years, also presented POI and AMH levels < 1 ng/mL followed the same PRP and IVF protocol. After two PRP sessions, her AMH levels improved similarly to Case 1. Despite an initial pregnancy, the patient experienced pregnancy loss.Conclusion: These findings suggest that PRP may improve ovarian response in women with POI undergoing IVF. Further studies are warranted.Keywords: in vitro fertilization, IVF (D005307), infertility (D007246), platelet-rich plasma, PRP (D053657), primary ovarian insufficiency, POI (D016649)